1993
DOI: 10.1038/ng0593-59
|View full text |Cite
|
Sign up to set email alerts
|

A molecular variant of angiotensinogen associated with preeclampsia

Abstract: Pregnancy-induced hypertension (PIH) is a heterogeneous disorder which complicates 5-7% of all pregnancies and remains a leading cause of maternal, fetal and neonatal morbidity and mortality. Severe preeclampsia is the most distinctive and life-threatening form; a multi-system disorder more common in first pregnancies, it is characterized by high blood pressure and proteinuria. In a series of Caucasian women with pregnancy-induced hypertension, we have observed a significant association of preeclampsia with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
222
2
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(242 citation statements)
references
References 14 publications
11
222
2
7
Order By: Relevance
“…We found a significant increased risk for preeclampsia in women carrying the C allele of the AT1R gene and the TT genotype of the AGT gene. Although the mechanism associating preeclampsia and RAS polymorphisms is still unclear, several studies have confirmed that particular RAS polymorphisms are positively associated with preeclampsia and that in addition to the classical circulating RAS, there are local de novo RAS that locally generate AngII [16,17]. It has also been reported [17] that the AGT gene may function as part of a spiral artery RAS that has a role in spiral artery remodeling and that the AGT 235T allele may be a marker of failed physiologic change, because the AGT expression may lead to elevated local AngII levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a significant increased risk for preeclampsia in women carrying the C allele of the AT1R gene and the TT genotype of the AGT gene. Although the mechanism associating preeclampsia and RAS polymorphisms is still unclear, several studies have confirmed that particular RAS polymorphisms are positively associated with preeclampsia and that in addition to the classical circulating RAS, there are local de novo RAS that locally generate AngII [16,17]. It has also been reported [17] that the AGT gene may function as part of a spiral artery RAS that has a role in spiral artery remodeling and that the AGT 235T allele may be a marker of failed physiologic change, because the AGT expression may lead to elevated local AngII levels.…”
Section: Discussionmentioning
confidence: 99%
“…Human linkage and association genetic studies have revealed the presence of polymorphisms in genes encoding key components of the RAS that account for the proportion of the variance in activity of this system [13][14][15]. Studies of these polymorphisms reported both positive [16,17] and negative association with preeclampsia [18,19]. However, although the association of each of these polymorphisms with preeclampsia has been studied extensively, there are no available data of the possible synergistic effect of these variants.…”
Section: Introductionmentioning
confidence: 99%
“…A single base change in codon 235 (235 Thr) results in the substitution of a threonine residue for methionine and is associated with increased plasma angiotensinogen concentrations in subjects with essential hypertension. A study of preeclamptic women from the United States and Japan reported that 235 Thr was associated with pre-eclampsia and that pre-eclamptic women possessing this variant had higher plasma angiotensinogen concentrations than did women homozygous for 235 Met (22). The maternal angiotensinogen gene was also implicated in a linkage study of pre-eclamptic pedigrees from Scotland and Iceland (23).…”
Section: Pregnancy-induced Hypertensionmentioning
confidence: 99%
“…It is in linkage disequilibrium with a T174M polymorphism, also frequently addressed. Available evidence suggests that the T allele of the M235T variant is associated with higher circulating angiotensinogen levels (∼20% in homozygous carriers) and increased blood pressure and preeclampsia (Jeunemaitre et al 1992b;Ward et al 1992;Staessen et al 1999). Some animal models indicate that increased AGT gene expression results in hypertension (Takahashi and Smithies 1999).…”
Section: Polymorphisms In the Angiotensinogen Genementioning
confidence: 99%